The Significance of Touch in Psychiatry Clinical and Neuroscientific Approaches - Müller-Oerlinghausen, Bruno; Eggart, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Touch is one of the fundamental media for interpersonal communication. Over recent decades, scientific efforts have been devoted to establishing the significance of touch, particularly affective touch, in the treatment and prevention of mental disorders and clarifying the underlying mechanisms of touch and massage therapy. This book contributes to this rapidly expanding area of research and gives new insights on recent clinical and experimental findings. A strong plea is made by the editors for well-designed clinical studies which require very special methodologies. A broad spectrum of various touch therapies are already available at present. Modern treatment and prevention of mental disorders should go beyond the pharmacological and psychotherapeutic approaches and should make use of the beneficial effects of touch therapies with the additional benefit of a very small risk of adverse outcomes.